Since "m1" and "m2" represent different masses, we can change them to different letters. This will make it easier to solve.
m1 = m
m2 = n
F = G*m1*m2/d^2 → F = Gmn/d^2
Steps to solve for d:
F = Gmn/d^2
~Multiply d^2 to both sides
d^2 * F = d^2 * Gmn/d^2
~Simplify
d^2 * F = Gmn
~Divide F to both sides
d^2*F/F= Gmn/F
~Simplify
d^2 = Gmn/F
~Take the square root of both sides
√d^2 = ±√Gmn/F
~Simplify
d = ±√Gmn/F
Since we are done solving for d, we can input "m1" and "m2" to replace "m" and "n".
d = ±√Gmn/F → d = ±√G*m1*m2/F
Therefore, the answer is [ d = ±√G*m1*m2/F ]
Best of Luck!